PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN PIUTANG, PERPUTARAN PERSEDIAAN, PERPUTARAN KAS, UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN DAN RETURN ON ASSET TERHADAP LIKUIDITAS PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nina Andriany Nasution; Hani Giofani Lumbantoruan (Jurnal Abdi Ilmu, 2021)
This study entitled "The Effect of Working Capital Turnover, Accounts Receivable Turnover, Inventory Turnover, Cash Turnover, Company Size, Company Growth And Return On Assets Towards Liquidity In LQ-45 Companies Listed On The Indonesia Stock Exchange". This study aims to analyze working capital turnover, accounts receivable turnover, inventory turnover, cash turnover, company size, company growth and return on assets on liquidity in LQ-45 companies with multiple regression analysis. The population in this study are LQ-45 companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The samples studied were 10 LQ-45 companies for the 2015-2019 period. The data used in this research is secondary data. The data were processed using multiple linear regression using SPSS Version 23.0. The results showed that partially working capital turnover, accounts receivable turnover, inventory turnover, cash turnover, company size, company growth and return on assets had a positive and significant influence on liquidity.